D-dimer surge and coagulation disorders in COVID-19 related pneumonia patients with cardiac injury: A case series. Issue 31 (31st July 2020) - Wang, Xingtong; Du, Beibei; Li, Jia; Wang, Shunan; Wang, Xiuxiu; Guo, MengYuan; Yang, Bo; Si, Daoyuan; Bai, Ou
Abstract: Background: Cardiac injury and coagulation disorders have been two increasing concerns in the management of patients with severe coronavirus disease (COVID-19). Coagulation disorders in COVID-19 patients with cardiac injury have not been characterized. Methods: We analyzed the data of five COVID-19 patients with cardiac injury who had D-dimer surge (defined as a rapid increase in the D-dimer level in 72 h, from <5–21 μg/mL) during hospitalization, which were extracted from a registered retrospective study (ChiCTR2000031301). Clinical data and data on changes in coagulation parameters were collected, verified, and characterized. Results: Among these five patients, four had pre-existing cardiovascular or cerebrovascular diseases. D-dimer surge was accompanied with prolonged prothrombin time (PT) and reduced platelet count (PLT) and fibrinogen level. Three patients had an ISTH DIC score of 5 and met the criteria for overt DIC. All five patients needed invasive ventilation support and were incubated 0 to 6 days after the first D-dimer upper reference limit (URL) was reached. All five patients died within 10 days after the first D-dimer URL was reached. All five patients had observed D-dimer URL results 1 to 3 days before death. Conclusion: D-dimer surge in COVID-19 patients with cardiac injury surely leads to worse in-hospital outcome. D-dimer surge and concomitant DIC can be the leading causes of in-hospital death. Pre-existing cardiovascular or cerebrovascular diseases might pose a higher risk for developing these coagulation disorders. These findings can serve as hypothesis generating and need further clinical trials to confirm.